Significance of Developing Path from Ideas Across Ideals to Principles and Norms - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Text "Significance of developing path from ideas across ideals to principles and norms" had been performed with the aim to depict that every formation of norms, in the framework of any law discipline, if we want to make them with adequate quality, has to go through four phases of developing modalities. At the outset, we have to form clear ideas oriented at the base of philosophical thinking and our law science discipline, of course, respecting knowledge of the complete law science. In the second phase of their development ideas have to be transformed into specific ideals toward we aspire, at such a way gradually manifest itself not only as law science ideals but also as specific political goals, which is third phase of thinking and developing, enabling at such a way that in the fourth phase, on the base of political, democratic, life, with the participation of the law science experts, previously formed ideas, ideals and principles can be transformed into precise and applicable norms. What is said is valid for every modern democratic society and state, and every discipline of law, science, and legislature.